Where are the Graphics? Communicating Legal Ideas Effectively Using Images and Symbols - Tania Leiman (Legal Education Review)
This paper seeks to explore the effective communication of legal ideas in the 21st century. It builds on ideas first presented in December 2015 at the Teaching Legal Analysis and Writing Skills Symposium, Melbourne Law School and developed in May 2016 at a Flinders Law School Research Seminar. It begins by discussing why communication about the law can benefit from using tools other than text, before moving on to a brief historical and theoretical overview of visual communication in the law. It canvases examples of best practice visual communication about the law before going on to seek to understand what this might mean for lawyers, legal education and legal educators.